2020
DOI: 10.1002/anie.201915882
|View full text |Cite
|
Sign up to set email alerts
|

Mercaptothiacalixarenes Steer 24 Copper(I) Centers to form a Hollow‐Sphere Structure Featuring Cu2S2 Motifs with Exceptionally Short Cu⋅⋅⋅Cu Distances

Abstract: Tetramercaptotetrathiacalix[4]arene (LH4) can be used as a coordination platform to bind four CuI ions at the thiolate and thioether S atoms. Donor ligands such as phosphanes can stabilize the resulting [LCu4] units, which then remain monomeric ([(Ph3PCu)4L]). In the absence of donor ligands, they aggregate, providing a hexamer ([LCu4]6) in high yields, with a hollow‐sphere structure formed by an unprecedented Cu24S48 cage that is surrounded by the organic framework of the calixarene chalices. Preliminary NMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…As in the di‐ and trinuclear complexes, discussed above, two of the aryl rings are oriented almost parallel to each other, while the other two are almost orthogonal (85.6°), so that the thiolate groups are pointing toward the interior of the complex. Each of the four gold atoms is coordinated by two thiolate functions, a thioether donor as well as a phosphine ligand, similarly as in case of the Cu ions in the compound [(Ph 3 PCu) 4 (MTC[4])] [7] . However, while in the latter the Cu atoms have a tetrahedral coordination sphere with Cu‐S distances that were all similar, in [(Me 3 PAu) 4 TlCl(MTC[4])] a see‐saw type arrangement is found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the di‐ and trinuclear complexes, discussed above, two of the aryl rings are oriented almost parallel to each other, while the other two are almost orthogonal (85.6°), so that the thiolate groups are pointing toward the interior of the complex. Each of the four gold atoms is coordinated by two thiolate functions, a thioether donor as well as a phosphine ligand, similarly as in case of the Cu ions in the compound [(Ph 3 PCu) 4 (MTC[4])] [7] . However, while in the latter the Cu atoms have a tetrahedral coordination sphere with Cu‐S distances that were all similar, in [(Me 3 PAu) 4 TlCl(MTC[4])] a see‐saw type arrangement is found.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we investigated the copper(I) chemistry of H 4 (MTC[4]) and found that [(Ph 3 PCu) 4 (MTC[4])] complexes are rather stable entities and are formed independently of the stoichiometry between ligand and metal precursor [7] . In the absence of phosphine co‐ligands [Cu 4 (MTC[4])] units are formed as well and subsequently stabilize by aggregation to a hexamer with a hollow ball structure [7] …”
Section: Introductionmentioning
confidence: 99%
“…Symmetry code: (') À1 + z, À1 + x, y; (*) 1Àx, À1 + z, y; (#) 1Àz, 0.5Ày, 1.5Àx; (+) À1 + x, 0.5Ày, 1.5Àz. [19] 93 3 of the 187 3 cavity remain empty. Considering the suggestion that a packing coefficient of around % 55 % is favorable for molecular cavities, [16] it is unlikely that a stable situation can be reached where other molecules permanently reside in the central cavity beside Et 2 NH.…”
Section: Communicationsmentioning
confidence: 99%
“…[14] DFT calculations on [LCu 4 ] 6 reproduced the rather short Cu···Cu distances (deviation of 0.083-0.031 depending on the functional used, see Supporting Information), and a similar value was predicted for an extract of the structure as depicted in Scheme 2 (right hand side), so that the phenomenon is intrinsic to the Cu 2 S 2 core with this ligation. (2), S4-Cu2-S5 88.341 (19), Cu2-S5-Cu3 148.08 (2). [19] Angewandte Chemie…”
mentioning
confidence: 99%
“…Among this rich class of cyclic oligosaccharides, α-/β-/γ- CDs are widely studied as hosts for a variety of organic molecular guests because of their suitable size, amphiphilic structures, and good availability. Compared to other synthetic host systems, e.g., crown ethers [ 7 , 8 , 9 ], calixarenes [ 10 , 11 , 12 ], cucurbiturils [ 9 , 13 , 14 ], and pillararenes [ 15 , 16 , 17 ], CDs are less toxic and/or exhibit good water solubility and biocompatibility [ 11 , 18 ]. Their facile covalent modification also renders them highly promising candidates as functional delivery systems [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%